Encouraging Digital Marketing Readiness for Cibaduyut MSMEs: Needs Analysis and Enhancement Strategies - Fauziah, Didah; Rohayati, Yati; Sagita, Boby Hera (International Journal of Innovation in Enterprise System, 2024)
This study aims to identify the need to improve the digital marketing readiness of Cibaduyut shoe and footwear craftsmen. Cibaduyut is one of the largest and oldest local shoe and footwear industry centers in Bandung City that is in demand by both national and international markets. However, several problems were found to be experienced by craftsmen, including the monetary crisis, which caused a decline in people’s purchasing power, the existence of the ASEAN-China free trade area (ACFTA), which facilitated the entry of imported products, digital developments, and globalization which brought significant changes to the decline in shoe and footwear sales, and the low understanding of craftsmen regarding digital marketing which resulted in craftsmen losing out to sellers who implemented digital marketing. This study applies the digital marketing readiness model and Refined Kano. Non-probability sampling was used for sampling with a purposive sampling technique. A survey of 100 Cibaduyut shoe and footwear craftsmen was conducted to assess 15 attributes of needs. Among these needs, nine attributes require improvement, while the remaining require further development.